0.8888888 = 8/9
2.8888888 = 26/9
-2.888888 = -26/9
Answer:
2022
Step-by-step explanation:
2 + 4x = y
y = 2 + 4(505)
y = 2 + 2020
y = 2022
Answer:
The Quotient Property.
Step-by-step explanation:
Since all three logarithms have the same base (base-5), and you are subtracting 6 and 3, to solve this all you need to do is 6 / 3 because of the Quotient Property.
You aren't multiplying anything, so you wouldn't use the Product Property.
You are not messing around with powers, so you wouldn't use the Power Property.
And you aren't using addition or multiplication, so you wouldn't use the Commutative Property.
Hope this helps!
The sum of the 8 terms of the series 1-1-3-5- ... -13 is -48
The given sequence is:
1,-1,-3, . . -13
and there are 8 terms.
The related series of this sequence is:
1-1-3-5- ... -13
Notice that the series is an arithmetic series with:
first term, a(1) = 1
common difference, d = -1 - (1) = -2
last term, a(8) = -13
To find the sum of the series, use the sum formula:
S(n) = n/2 [(a(1) + a(n)]
Substitute n = 8, a(1) = 1, a(n) = a(8) = -13 into the formula:
S(8) = 8/2 [1 + (-13)]
S(9) = 4 . (-12) = -48
Learn more about sum of a series here:
brainly.com/question/14203928
#SPJ4
In order to use the elimination method, we have to multiply the equation by some number, so that one of the variable has the same coefficient.
For example, multiplying the first equation by 3 and the second by 2 gives the following, equivalent system:
![\begin{cases}6x-15y=33\\6x+4y=14\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D6x-15y%3D33%5C%5C6x%2B4y%3D14%5Cend%7Bcases%7D)
Now, we can subtract the two equations, and we will cancel (eliminate) the x variable:
![-19y=19 \iff y=-1](https://tex.z-dn.net/?f=%20-19y%3D19%20%5Ciff%20y%3D-1%20)
Now that y is known, plug it into one of the equations: for example, if we use the first one we get
![2x+5 = 11 \iff 2x = 6 \iff x=3](https://tex.z-dn.net/?f=%202x%2B5%20%3D%2011%20%5Ciff%202x%20%3D%206%20%5Ciff%20x%3D3%20)